Implementation of Behavioristic Learning Theory in Learning Islamic Religious Education (PAI) at Labschool Cibubur High School - Doni, Doni; Kalsum, Umi; Rashid, Rabiatul Adawiyah Ahmad (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
Nowadays there is a phenomenon of moral decadence, namely frequent cases of bullying, sexual violence, bullying and character crises in the world of education. Here researchers are interested in how to implement Behavioristic Learning Theory in Islamic Religious Education Learning at SMA Labschool Cibubur which aims to shape behavior and hopefully break moral decadence. This research uses qualitative methods with data collection techniques of observation, interviews and document study. The results of this research show that based on Edward Thorndike's behavioristic theory, known as Connectionism theory, learning is a process of connection between stimulus and response which leads to changes in behavior, with readiness to accept changes in behavior (law of Readiness), given repetition (Law of Exercise) and awarded (Law of Effect), then the implementation of behaviorist learning theory in Islamic Religious Education learning from Labschool Cibubur High School activities as well as in classroom learning, children are evaluated and familiarized with evaluation activities for the morning prayer, procedures for ablution, purification, reading the Al-Quran, Tajwid and Makharijul Huruf, helping parents, how to socialize with the opposite sex, social media etiquette. Also from familiarization with student organization activities, leadership training, extracurricular activities, activities to strengthen Wiyata Mandala insight, 7 basic values of Labschool, 15 cultures of life at school, and 18 life skills at Labschool.